2013
DOI: 10.1371/journal.pgen.1003721
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stresses Disrupt Telomere Length Homeostasis

Abstract: Telomeres protect the chromosome ends from degradation and play crucial roles in cellular aging and disease. Recent studies have additionally found a correlation between psychological stress, telomere length, and health outcome in humans. However, studies have not yet explored the causal relationship between stress and telomere length, or the molecular mechanisms underlying that relationship. Using yeast as a model organism, we show that stresses may have very different outcomes: alcohol and acetic acid elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 55 publications
4
93
0
1
Order By: Relevance
“…8A). Since steady-state telomere length decreases upon growth at an elevated temperature in wild-type yeast strains (69), these data suggest that the exaggerated decrease in telomere length that occurred in the noncomplemented strain was specifically attributable to decreased SRP1 function.…”
Section: the Est1-mut123(fl) Mutant (Bottom) Fluorescence Microsmentioning
confidence: 85%
“…8A). Since steady-state telomere length decreases upon growth at an elevated temperature in wild-type yeast strains (69), these data suggest that the exaggerated decrease in telomere length that occurred in the noncomplemented strain was specifically attributable to decreased SRP1 function.…”
Section: the Est1-mut123(fl) Mutant (Bottom) Fluorescence Microsmentioning
confidence: 85%
“…In this respect, physiological pathways and mechanisms for bio-behavioral factors and cancer progression was reviewed (Lutgendorf et al 2011). In addition, molecular study with telomerase activity associated telomere length with environmental and psychological stress (Epel et al 2010;Romano et al 2013). A result of interest, however, was recently published demonstrating that the effects of personality traits and depression on cancer risk and survival appear to be extremely as small as the data obtained from prospective cohort studies in population-based and clinical databases Nakaya 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2H). It was previously reported that prolonged heat shock (at 37°C) causes telomere shortening in yeast (32,33). To understand whether telomere shortening is responsible for the derepression of subtelomeric chromatin, we wanted to find out whether transient heat shock also leads to such changes in the telomere structure.…”
Section: Hs or Hsp82 Overexpression Induces Transcriptional Downregulmentioning
confidence: 99%
“…An elongated telomere track leads to the increased inheritance of the silenced subtelomeric state and is independent of yeast chromatin assembly factor 1 (yCAF-1). In another study, it was reported that prolonged exposure to heat stress (37°C) as well as Hsp82 overexpression led to telomere shortening in wild-type cells (32,33). Thus, it is important to understand whether transient heat shock causes any change in telomere structure and can thereby influence telomere silencing.…”
Section: Figmentioning
confidence: 99%